PENGARUH BEBAN GAJI DAN TUNJANGAN TERHADAP TOTAL LABA PERIODE BERJALAN PADA PT TELEKOMUNIKASI INDONESIA TBK PERIODE 2016-2023 - Soetedjo, Louis Lewinsky (Fakultas Ekonomi Prodi Akuntansi, 2025)
Salaries and benefits are major components of a company's operational costs that can influence profitability. This study aims to analyze the effect of salaries and benefits expenses on total income for the period at PT Telekomunikasi Indonesia Tbk from 2016 to 2023. The research method used is simple linear regression with secondary data obtained from the annual financial reports of PT Telekomunikasi Indonesia Tbk. The analysis was conducted to determine the relationship between salaries and benefits expenses as the independent variable and total income for the period as the dependent variable. The results show that salaries and benefits expenses significantly affect total income for the period, with a regression coefficient value of 0.2832 and an R Square of 0.9274. The significance test resulted in a p-value of 0.00000000000000000121, indicating a highly significant relationship between the two variables. Keywords: Salaries, benefits, total income for the period, linear regression, PT Telekomunikasi Indonesia Tbk.